Trauma Scoring and Forensic Medicine - Günay, Yasemin (The Bulletin of Legal Medicine, 1999)
A number of trauma scoring systems have been developed in order to evaluate and measure the severity of physical injury. In this paper, some of important trauma scoring systems are presented, and their utility and applicability are in forensic medicine. Key words: Trauma scoring, forensic medicine, applicability.